Management of Splenomegaly (Pleehodara) with Classical Herbomineral Drugs (International Journal of Ayurveda and Pharma Research, 2024)
With proper knowledge and timely intervention, Ayurvedic herbomineral drugs can reverse diseases without any side effect. Splenomegaly is a rare disorder that affects 2% of Americans in total, according to estimates of prevalence. It is need of time to work more over the traditional medicine like Ayurveda to search new dimension in this field. Some Ayurvedic seers have mentioned Yakritodar in separate chapters and some others has included under Udararoga heading. It was assumed as Kapha-pitta disorders among various herbal and herbomineral drugs they have focused in prescribing Kshara and drugs which can pacify Kapha-pitta. Drugs like Yakritplihari lauha, Pippali churna, Rohitakarista, Arogyavardhini vati are not only effective in reducing the size of spleen but also provide relief in many other systemic symptoms. The total duration of treatment was 3 months. The patient was assessed for improvement in hematological parameters, ultrasound report and signs and symptoms. Hence, presenting this case is evidence to demonstrate the effectiveness of 3 months of Ayurvedic treatment in managing splenomegaly.